Examining coaches' perceptions of how organisational justice affects organisational support - Ooi, Cheng Lee; Yusof, Aminuddin; Soh, Kim Geok; Omar, Zoharah (Human Resource Management Academic Research Society, 2017)
This study aimed to examine how school volunteer coaches perceived the relationship between four-dimensional of organisational justice (procedural, distributive, interpersonal, and informational justices) and perceived organisational support. A cross-sectional correlational research mail survey was conducted on 750 Malaysian school volunteer coaches by applying proportionate stratified random sampling techniques. The data were analysed using IBM SPSS and structural equation modeling with AMOS. Results showed all dimension of organisational justice with the exception of procedural justice are associated with perceived organisational support. This finding has contradicted a majority of past literature findings that procedural justice has the strongest influenced on organisational outcomes. The results suggest the need to craft fair procedures or policies that allow freedom of voice in the volunteer coach management system. A sound system of procedural justice is important for the organisation to demonstrate its support towards volunteer coaches, in order to attract their emotional attachment and loyalty to coach for the organisation in the long run.